Development Of New Self-potential Acquisition Technique For Ground Subsurface Investigation - Jinmin, Mark (2024)
Self-potential (SP) method is a passive geoelectrical method. It measured the natural potential differences which exist between any two points on the ground. The points are measured using an electrode known as the roving electrode and the base electrode. In the SP method, these electrodes are often called ‘porous pots’ which are designed not to create any chemical potential once they are contacted on the ground. A reference electrode is used as a base electrode, and the second electrode is used to measure the potential on the ground. The primary research is to introduce the practical techniques in SP data acquisition which is Self-Potential Enhancement Technique (SPET). SPET is a combination of techniques which are the electrode calibration technique (EC), the optimum electrode time technique (OET), and the closed loop. Using a pair of electrodes consumes more time and energy during data acquisition. Hence, the EC is to calibrate and correct the electrode error during data measurement, which is able to use multiple electrodes. An inconsistent time period for mitigating an electrode on the ground can lead to inaccurate self-potential data readings. Thus, the OET purpose is to identify the time frame for an electrode to be in equilibrium on the ground. The SP has an electrode configuration for acquiring the electrical potential data such as gradient and fixed base. The gradient technique has some disadvantages in the data quality, such as cumulative error, electrode polarization, drift effect, time-varying potential, soil contact effect, and reading errors.